2014
DOI: 10.1097/fjc.0000000000000043
|View full text |Cite
|
Sign up to set email alerts
|

Ang-(1–7) Offers Cytoprotection Against Ischemia–Reperfusion Injury by Restoring Intracellular Calcium Homeostasis

Abstract: Accumulating evidence indicates that angiotensin-(1-7) [Ang-(1-7)] offers protective effects against ischemia-reperfusion (I/R) induced arrhythmias and contractile dysfunction, which are related to disturbances of intracellular calcium homeostasis. However, whether or not Ang-(1-7) regulates intracellular calcium in I/R is not clear. To shed light on this issue, we carried out studies with a cellular model of simulated I/R in isolated rat ventricular myocytes and measured calcium transients using laser scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…In addition, icaritin reduced the increase in Ca 2+ release elicited by t-BHP treatment, further suggesting that icaritin may protect mitochondrial integrity by preventing Ca 2+ overload and ROS production. In line with this result, a recent study also demonstrated that angiotensin-(1-7) confers protective effects against ischaemia-reperfusion-induced cardiac dysfunction through inhibiting calcium release and ROS production (Wang et al, 2014). We speculate that t-BHP-mediated Ca 2+ entry into cardiomyocytes involves the accumulation of ROS and the opening of mitochondrial membrane pores.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, icaritin reduced the increase in Ca 2+ release elicited by t-BHP treatment, further suggesting that icaritin may protect mitochondrial integrity by preventing Ca 2+ overload and ROS production. In line with this result, a recent study also demonstrated that angiotensin-(1-7) confers protective effects against ischaemia-reperfusion-induced cardiac dysfunction through inhibiting calcium release and ROS production (Wang et al, 2014). We speculate that t-BHP-mediated Ca 2+ entry into cardiomyocytes involves the accumulation of ROS and the opening of mitochondrial membrane pores.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, the direct effect of Ang-(1–7) on intracellular Ca 2+ mobilization in myocytes is unclear, since previous studies provided conflicting findings. (12;18;19) Furthermore, the ever-emerging body of experimental evidence continues to support that an important subset of cardiovascular actions of Ang-(1–7) is related to its bradykinin (BK) potentiating activity and its facilitation of nitric oxide (NO) release. (6;8;12;20;21) It is reasonable to speculate that the effects of Ang-(1–7) on myocyte may via Ang-(1–7) receptors while be coupled with NO/BK-mediated mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the absence of MasR in cardiomyocytes from MasR-KO mice elicits opposite effects over Ca 2+ handling [114]. However, the participation of MasR agonists on Ca 2+ management is still unclear [115,116]. On this regard, as the majority of GPCRs, MasR shows a response depending on the agonist used [117].…”
Section: Mas Signaling Pathwaysmentioning
confidence: 94%
“…It is widely known that I/R induces arrhythmias and contractile dysfunction in cardiac cells and that Ang-(1-7) has a cardioprotective role. In vitro studies showed that Ang-(1-7) improves Ca 2+ homeostasis in cardiomyocytes subjected to simulated I/R [116]. Regarding to defective electrical coupling in cardiac cells and ischemia-associated arrhythmias, Ang-(1-7) improves cardiomyocyte communication and might improve impulse propagation [124].…”
Section: Angiotensin-(1-7) and Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation